Bilateral optic neuropathy in acute cryptococcal meningitis - Qi, Zhe Ngoo; Li, Min Evelyn Tai; Wan Hitam, Wan Hazabbah; John, Tharakan (Elsevier, 2016)
We reported a case of cryptococcal meningitis presenting with bilateral optic neuropathy in an immunocompetent patient. A 64-year-old Malay gentleman with no medical comorbidities presented with acute bilateral blurring of vision for a week, which was associated with generalised throbbing headache and low grade fever. He also had somnolence and altered consciousness. Visual acuity in both eyes was no perception of light with poor pupillary reflexes. Extraocular muscle movements were normal. Anterior segments were unremarkable bilaterally. Fundoscopy revealed bilateral optic disc swelling. CT scan of the brain showed multifocal infarct, but no meningeal enhancement or mass. Cerebrospinal fluid opening pressure was normal, while its culture grew Cryptococcus neoformans. A diagnosis of cryptococcal meningitis with bilateral optic neuropathy was made. Patient was treated with a six-week course of intravenous fluconazole and started concomitantly on a fortnight's course of intravenous amphotericin B. After that, his general condition improved, but there was still no improvement in his visual acuity. On reviewing at two months post-initiation of treatment, fundi showed bilateral optic atrophy. Bilateral optic neuropathy secondary to cryptococcal meningitis was rare. The prognosis was guarded due to the sequelae of optic atrophy. Anti-fungal medication alone may not be sufficient to manage this condition. However, evidence for other treatment modalities is still lacking and further clinical studies are required.